The Effect of Nurse Navigator program on Activity Daily Living in elderly hospitalized - Limoochi, Sahar; Mehraban, Marzieh Adel; Keshvari, Mahrokh (International Journal of Psychosocial Rehabilitation, 2020)
The chronic diseases and increasing the probability of hospitalization are one of the critical consequences of the aging population, which may raise the probability of hospitalization related complications prevention of side effects and disease is one of the nurses duties. This study is designed to determine their influence of nurse navigator on patient activities of daily living (ADL). This experimental study was quasi-experiment intervention that it conducted on 58 elderly patients hospitalized that are divided into two groups of control and experimental. In this paper, the role of the nurse navigator was designed and then implemented by the researcher with a description of its main tasks. Collecting data tools was: patient right charter questionnaire (r=0.84), modified Barthel index (MBI) (r=96-99%) and demographic characteristics. The designed program was implemented only in the intervention group. Then Activities of daily living (ADLs) were measured once a month and then three months after the intervention using the Barthel index. Finally, the experimental results were analyzed using the latest version of SPSS software. The mean ages of participants in experiment and control groups were measured as 69.9 and 72.39 years, respectively. Meanwhile, before implementing the study, the independent t-test indicated that the mean score of ADLs, in the experimental group (73.20±14.02) and the control group (71.57±16.36) before the intervention did not have a significant difference (P>0.05). Nevertheless, analysis of covariance in both groups revealed that the mean score of ADLs one month after intervention in the experimental group was calculated as 90.03±8.03, whereas in the control group, it was 70.21±22.87 three months after the intervention. In the experimental group 91.20±6.77 and in the control group was 71.36±23.40, in the experimental group was significantly higher than the control group (P <0.05). The results of this study shows that the nurse navigator plan is effective to increasing ADL level , due to the study we can say that implementing the nurse navigator plan can be known as an important step in preventing the elderly from overacting as well as empowering them to increase their independence in ADLs.